Wrong-Site Surgery in Orthopaedics: Prevalence, Risk Factors, and Strategies for Prevention. Issue 1 (26th January 2016) - Santiesteban, Lauren; Hutzler, Lorraine; Bosco, Joseph A.; Robb, William
Abstract : The incidence of wrong-site surgery in orthopaedics is unknown. This is due to a lack of data regarding the exact numbers of surgical procedures performed and a lack of a uniform mandatory error reporting infrastructure. Twenty-one percent of hand surgeons, 50% of spinal surgeons, and 8.3% of knee surgeons surveyed have reported performing at least one wrong-site surgery during their career. Every orthopaedic surgeon, no matter his or her orthopaedic subspecialty, is at risk for completing a wrong-site surgery during his or her career. Prevention of wrong-site surgery should remain a priority for the orthopaedic community. Surgeon leadership, commitment, and vigilance are critical to improve patient safety by ensuring that validated safety processes are used in all orthopaedic settings including effective surgical team communication, checklists, and routine collection and analysis of quality and safety data.